Call of Pastors and Religious Teachers for Virtual Theology Through Social Media at the Evangelical Christian Church in Minahasa - Stevi F.CH. Wowor; Benny B. Binilang; Johanna P. Setlight; Wolter Weol (International Journal of Education, Information Technology, and Others, 2023)
This study aims to describe and analyze understanding and practice, supporting factors, obstacles and solutions, as well as the implications of GMIM Priests' and Religious Teachers' Virtual Theology through social media at the Evangelical Christian Church in Minahasa. To achieve this goal, qualitative research methods are used with phenomenological analysis. To collect field data this research uses participatory observation techniques, interviews and documentation studies. Based on the results of the research that has been done, it can be concluded that Pastors and Religion Teachers of GMIM state that evangelism and PAK are part of their service calling which is implemented in various forms of posting, because it has become a necessity in service. The implication is that the Minahasa Evangelical Christian Church should equip its servants to be able to do virtual theology on social media, have dogmatic teachings of the church based on virtual theology, respond to church services in the form of Hybrid Church and GMIM Virtual Reality, because social media has become a medium for evangelism and PAK in the revolutionary era. Industry 4.0 and through evangelism and PAK on social media, a person and or a group of people can get the motivation of faith, hope and the spirit of sharing love.